Supportive Care in Cancer Cachexia: Meeting the Unmet Need - Shankar, Abhishek; Singh, Pritanjali; Mishra, Seema; Gupta, Shipra; Roy, Shubham; Saini, Deepak; Bharati, Sachidanand Jee; Seth, Tulika; Maheshwari, Apoorva; Kumar, Ajeet (Asian Pacific Journal of Cancer Care, 2022)
Cachexia is characterized by loss of appetite, weight loss and tissue wasting, accompanied by a decrease in muscle mass and adipose tissue, affecting approximately 50% of cancer patients and contributes to decreased quality of life of patients, reduced tolerance to chemotherapy, and decreased survival. Current therapies focus on maintenance of physical function, quality of life, and reduction of distress in patients and their families rather than definitive treatment for the underlying pathophysiology. Consistent with evolving guidelines for the treatment of cachexia, current models take a multidisciplinary approach, with patients generally seeing a physician, nutritionist or dietician, and physiotherapist sequentially. This is routinely supplemented by psychosocial support, whether within the program or via referral. Early intervention and attention to nutritional status are essential in patients with anorexia-cachexia syndrome. Pharmacological interventions for neoplastic cachexia include drugs that stimulate the appetite: megestrol acetate (MA) and dronabinol; cytokine inhibitors (such as cyproheptadine, thalidomide, pentoxifylline and an eicosapentaenoic acid (EPA)); and anabolic agents such as nandrolone decanoate, oxandrolone and corticosteroids. This review will discuss about the role of supportive care in cancer cachexia with a special emphasis on nursing oncology perspective.